2022
DOI: 10.3389/fphar.2022.927087
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Ginsenoside Rb2 Against Cyclophosphamide-Induced Immunosuppression in Mice

Abstract: Ginsenoside Rb2 (Rb2), a fundamental saponin produced and isolated from ginseng (Panax ginseng C.A. Meyer), has a wide range of biological actions. The objective of this investigation was to see if ginsenoside Rb2 has any immunomodulatory properties against cyclophosphamide (CTX)-induced immunosuppression. For the positive control group, levamisole hydrochloride (LD) was used. We discovered that intraperitoneal injection of Rb2 (5, 10, 20 mg/kg) could relieve CTX-induced immunosuppression by enhanced immune or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…Consistent with the investigations of other researchers, [32][33][34] Food & Function Paper our current research indicated that CTX could decrease the body weight, spleen weight, and thymus weight in BALB/c mice, which indicated that CTX could cause damage to the immune system in the mice; however, the supplementation of BC encapsulated by liposomes improved these adverse alterations and exhibited a better effect than BC alone (Fig. 3 and 4).…”
Section: Bovine Colostrum Encapsulated By Liposomes Exhibited Better ...supporting
confidence: 91%
“…Consistent with the investigations of other researchers, [32][33][34] Food & Function Paper our current research indicated that CTX could decrease the body weight, spleen weight, and thymus weight in BALB/c mice, which indicated that CTX could cause damage to the immune system in the mice; however, the supplementation of BC encapsulated by liposomes improved these adverse alterations and exhibited a better effect than BC alone (Fig. 3 and 4).…”
Section: Bovine Colostrum Encapsulated By Liposomes Exhibited Better ...supporting
confidence: 91%
“…Ginsenosides have effects including enhancing T cell proliferation, inhibiting apoptosis, and indirectly inhibiting the growth of tumor cells 43 . Ginsenosides can improve the immunity of mice, reduce the expression of PD-L1 induced by chemoresistance, and restore the cytotoxicity of T cells toward cancer cells 44 . Aconite alkaloids can achieve anti-tumor effects by reducing the spreading ability of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Liposomes are mature and efficient drug delivery systems that demonstrates efficient cellular internalization, thereby reducing drug toxicity in vivo [13,14] . Further, ginsenosides are known to have various pharmacological activities, such as antitumor [15,16] , anti-inflammatory [15,17] , and immune regulation effects [18,19] . Additionally, studies have demonstrated that ginsenosides, with a steroid structure similar to that of cholesterol and attached sugar moieties, can replace cholesterol and form liposomes with phospholipids [20] [Supplementary Figure S1, http://links.lww.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these glycosided bind to the glucose transporter 1 (GLUT1) protein, which is highly expressed in tumor cells and promotes Rk1/CTX-Lip accumulation in tumor tissues [22] . Furthermore, Rk1 can improve cellular and humoral immunity [18,19] , and synergistically enhance the anti-prostate cancer efficacy of CTX while reducing immunosuppression and hematotoxicity during treatment [23] .…”
Section: Introductionmentioning
confidence: 99%